Randomised study shows that repeated self-sampling and HPV test has more than two-fold higher detection rate of women with CIN2+ histology than Pap smear cytology - Gustavsson, Inger (Br J Cancer, 2018)
BACKGROUND: This randomised study compared the detection rate of cervical intraepithelial neoplasia-positive (CIN2+) based on histology in women performing repeated self-sampling of vaginal fluid (VF) for human papillomavirus (HPV) test with a control group following the ordinary screening by Pap smear cytology. METHODS: 36390 women aged 30–49 years scheduled for invitation to organised screening were randomised in two groups, one to perform self-sampling of VF for HPV test (n=17 997, HPV arm) and the other group to perform screening by PAP smear cytology (n=18 393, control arm). HPV positive women in the HPV arm repeated the self-sampling and the HPV test on average 4.4 months later and those with two consecutive positive HPV tests were referred to colposcopy. Outcome was CIN2+ based on histology during 18-month follow-up. RESULTS: Participation rate was 47% in the HPV arm and 39% in the control arm. The HPV prevalence in the first self-sampling was 6.9%, and 71% of these women were HPV positive in their second test. For the per-protocol approach, cumulative prevalence of histological CIN2+ in the HPV arm was 20.2 per 1000 women screened as compared to 10.8 in the control arm. The cumulative prevalence of CIN2+ diagnosed per 1000 years screened was 160.8 in the HPV arm as compared with 25.4 in the control arm. CONCLUSIONS: Repeated self-sampling of VF and HPV test had more than a two-fold higher discovery rate of CIN2+ per 1000 women screened as compared with PAP smear cytology.